Profil Konsep Diri Remaja Putus Sekolah Di Jorong Taruyan Kecamatan Matur Kabupaten Agam - Sari, Eka Puspita; Kasih, Fitria; Zaini, Ahmad (Bimbingan dan Konseling, 2013)
This research was based on the phenomenon in the field that caused by environmental changes that experienced by adolescents who drop out of school make changes experiences in social interactions with the environment and themselves, most of dropout adolescent feel insecure and feel not accepted in society. Based on this study researchers raised concerns about: What is the profile of self-concept adolescent dropout in Jorong Taruyan Matur Agam District. This research aims to describe: 1) Self-concept profile dropout adolescent based on self- knowledge aspect. 2) Self-concept profile dropout adolescent based on hope themselves in the future. 3) Self-concept profile dropout based on self-assessment aspects. This research was a descriptive research. The population was dropout adolescent total of 11 people. The samples in this research were taken from a population, so, the technique to take the sample, namely: total sampling that samples taken from the population, instrument used was a questionnaire and interviews, while the technique analyzed using percentages. The result of this research revealed that: 1) Self-concept dropout adolescent profil from self- knowledge aspect are pretty well. 2) Self-concept dropout profil from themselves hope in the future aspect on good criteria. 3) Self-concept dropout adolescent profil from self-assessment aspects on criteria quite well.